2018
DOI: 10.1128/jb.00521-17
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Membrane Topography of the Vibrio-Type Secretin Complex from the Type 2 Secretion System of Enteropathogenic Escherichia coli

Abstract: The ␤-barrel assembly machinery (BAM) complex is the core machinery for the assembly of ␤-barrel membrane proteins, and inhibition of BAM complex activity is lethal to bacteria. Discovery of integral membrane proteins that are key to pathogenesis and yet do not require assistance from the BAM complex raises the question of how these proteins assemble into bacterial outer membranes. Here, we address this question through a structural analysis of the type 2 secretion system (T2SS) secretin from enteropathogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 73 publications
3
49
0
Order By: Relevance
“…Based on sequence analysis, the authors previously proposed that the EPEC secretin belongs to the Vibrio-type subfamily (14). In agreement with sequence similarities, a similar structural architecture can be seen between the two Vibrio-type secretins, i.e., the EPEC structure from the work of Hay et al (6) and the Vibrio structure from the work of Yan et al (15), with loops extending from the extracellular side to form the typical cap gate (Fig. 1).…”
supporting
confidence: 65%
See 3 more Smart Citations
“…Based on sequence analysis, the authors previously proposed that the EPEC secretin belongs to the Vibrio-type subfamily (14). In agreement with sequence similarities, a similar structural architecture can be seen between the two Vibrio-type secretins, i.e., the EPEC structure from the work of Hay et al (6) and the Vibrio structure from the work of Yan et al (15), with loops extending from the extracellular side to form the typical cap gate (Fig. 1).…”
supporting
confidence: 65%
“…Overall, with their structure-based BLAST experiment, Hay et al (6) revealed that the previous T2SS secretin classification, i.e., Vibrio and Klebsiella types (14), is definitely structurally relevant. Moreover, in providing an additional high-resolution 3D structure of a secretin, these authors are giving us a reminder of the structural diversity existing among T2SS secretins and are lending support to the existence of subtle functional differences.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Although no clear symmetry could be observed, nanogold labelling suggested that there are 14 subunits per secretin complex . From recent near‐atomic resolution cryo‐electron microscopy models of secretins from the type 2 secretion system and previous mutagenesis experiments on the pIV gate regions , we can extrapolate some information about the structure and function of pIV. Secretins form homo‐oligomeric complexes comprised of 15 copies of the secretin subunit.…”
Section: Filamentous Phage Life Cycle: Phage Egressmentioning
confidence: 92%